Design of computer network based on microtic router os in smp negeri 1 kota agung - Syndi Anggriani; Apriansyah (International Journal Cister, 2022)
SMPN 1 Kota Agung Lahat Regency is one of the junior secondary level public education institutions in the Lahat area. To support teaching and learning activities at SMPN 1 Kota Agung requires accurate and fast information in supporting services for their students. Currently SMPN 1 Kota Agung is not optimal in utilizing the Kant of technology to support teaching and learning activities, currently SMPN 1 Kota Agung is still experiencing difficulties in carrying out online teaching and learning activities due to the unavailability of an adequate internet network, this causes delays in sending assignments given by teachers to students which students have to come to school. In addition, there are obstacles experienced by the school in terms of sending reports to Dapodik because of this internet network problem as well. There are also other problems that exist at SMPN 1 Kota Agung in transferring data or files on each computer still using hardware such as Flashdisk, USB, this is vulnerable to the exchange of computer viruses who attacked the computer at SMPN 1 Kota Agung. Therefore in need a system to support this process by building and developing a local area network (LAN) and wireless fidility (WiFi) design. For this reason, the researchers conducted a study entitled "Designing a Computer Network Based on Mikrotik Router OS at SMP Negeri 1 Kota Agung" with the aim of making a computer network design available that can be implemented in SMP Negeri 1 Kota Agung.